Designs on the public : the private lives of New York's public spaces - Miller, Kristine F. (University of Minnesota Press, 2007)
Kristine F. Miller delves into six of New York's public spaces, including Times Square, Trump Tower, and Sony Plaza, to trace how design influences their complicated existence. Design is, in Miller's view, complicit in regulation of public spaces in New York City to exclude undesirables and privilege commercial interests, and in this work she shows how design can reactivate public space and public life.